ACCELERATING LEARNING THROUGH VEDIC MATHEMATICS: A COMPARATIVE AND PEDAGOGICAL INVESTIGATION - Mahajan, Monica (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Vedic Mathematics, an ancient computational framework derived from Indian scriptures and later systematized by Bharati Krishna Tirthaji, provides simplified and intuitive techniques for arithmetic operations. This study explores its pedagogical value in enhancing computational speed and accuracy among high school students. Using a quasi-experimental design involving 60 students divided into control and experimental groups, the study identifies a statistically significant improvement in calculation speed and error reduction in the Vedic Mathematics-trained group. The paper also discusses the integration of Vedic techniques into contemporary curricula, the cognitive benefits observed, and the limitations in applicability beyond foundational arithmetic. Implications for teaching practice and directions for further research are proposed. Keywords: Vedic Mathematics, mental math, curriculum integration, cognitive load, educational pedagogy, computational efficiency